(3GdETGQGJ hGdJfHjgGJs - (3GdHdNj, CHh Ydj, GHf SjfG, GdQFjS, TQa Gdedc, GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG, (B428 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3bGd GdTjN gPg GTGQGJ Edi CUhd hJfHjgGJ Ydi Led jSJHUQ HgG ef JjSQ dg hdG jfJaY HGdGUQM efgG ef JYSQ Ydjg hGdJcdGf hGdJhajb hCf CYjO hUjJj hCcQQ GdJeGSj Cf jVf HeG jTJed Ydjg (B...s
(3BNQgG (B:s
... (3hCeG cHQi GdbjGS ajOd YdjgG bhdg hPdc Ybd efg dPGJg jYfj JYbdg dchf PGJg YGbdI dPdc GdTjA JYbd efg dPGJg HhLg aEf GdYde HGdJUOjb Yde HJUhQ GdehVhY dSJ Cbhd gh Yde HJUhQ GdehVhY (B...s
(3eDWQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\241s
(3cTa GdXfhf (B1\81s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs